Plantar fasciopathy: A current concepts review - Monteagudo, Manuel (EFORT Open Rev, 2018)
Plantar fasciopathy is very prevalent, affecting one in ten people in their lifetime. Around 90% of cases will resolve within 12 months with conservative treatment. Gastrocnemius tightness has been associated with dorsiflexion stiffness of the ankle and plantar fascia injury. The use of eccentric calf stretching with additional stretches for the fascia is possibly the non-operative treatment of choice for chronic plantar fasciopathy. Medial open release of approximately the medial third of the fascia and release of the first branch of the lateral plantar nerve has been the most accepted surgical treatment for years. Isolated proximal medial gastrocnemius release has been reported for refractory plantar fasciopathy with excellent results and none of the complications of plantar fasciotomy. Cite this article: EFORT Open Rev 2018;3:485-493. DOI: 10.1302/2058-5241.3.170080.